Effect of Managerial Competencies on Small Medium Enterprise Creation in Awka South Local Government Area - Ogbara, Samuel; Chukwunwa, Chinedu (PT.KARYA GEMAH RIPAH, 2025)
This study investigated the effect of Managerial competencies on small medium enterprise creation in Awka South Local Government Area. The research design was descriptive research design. The study has a total population of 1453. The population of the study comprised of owners and employees in SMEs in Anambra State. Taro Yamane’s formula was applied to determine a sample size of 314. Simple random sampling technique was used in selecting the sample from the population of the study. Primary source of data collection was in data collection. The respondents’ demographics was presented in frequency tables and analyzed using simple percentage. The study found that management competencies help SMEs to coordinate the everyday activity of the business, develop broad-based investment planning and implementation. The study recommended that government should establish centres that teaches management competencies so as to help SMEs owners to coordinate the everyday activity of the business.